Oyster Shell Waste (Crassostrea Gigas) as A Cheap Adsorbent for Adsorption Of Methylene Blue Dyes: Equilibrium and Kinetics Studies - Muhammad Muhammad; Meriatna Meriatna; Nia Afriani; Rizka Mulyawan (International Journal of Engineering, Science and Information Technology, 2021)
In this study, Oyster (Crassostrea gigas) shell powder which contains calcium carbonate (CaCO3) was converted into calcium oxide (CaO). The Oyster shell powder that had been activated was utilized for the adsorption of the methylene blue (MB) dyeing material, which is one of waste water concerns. Oyster shells were crushed and sieved into 100 mesh sized powder and then calcinated at a temperature of 600â„ƒ and 800â„ƒ both for 4 hours period. To determine the adsorption equilibrium, methylene blue (MB) solution was used with varying concentration from 10 to 50 mg/L in which the adsorbent weighing 3 g was put into a conical flash and shaken until the adsorption equilibrium was reached. As for the adsorption kinetics, 250 mL MB solution was used with initial concentrations of 10, 20 and 30 mg/L, with an adsorbent weight of 3 g and a solution at pH 11 for each concentration. The evaluation of the experimental data from the adsorption process is well explained by the Freundlich equation, with the correlation coefficient value (R2) found to be 0.9999, where the value of the adsorption intensity (n) is close to unity; this shows that the adsorption is multilayer or in other words the adsorption energy is heterogeneous. The kinetics study also shows that pseudo second-order model is the most applicable to the adsorption process. From the pseudo-second-order model, with the correlation coefficient between 0.9984 - 0.9999 can explain that the methylene blue (MB) adsorption process is chemically based sorption or in other words termed as chemisorption.